Application Of Thiol Protease From Frangipani Stem (Plumeria obtusa) As A Coagulant Agent In Cream Cheese Production - Laksanawati, Trias Ayu; Khirzin, M. Habbib; Ersa, Fahmi; Wiralatif, Aditya (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
Frangipani contains thiol protease enzymes, particularly in its stem. The stem's thiol protease qualifies as a vegetable rennet, which can be used as a milk coagulant to substitute animal-based rennet in cream cheese. This study aims to determine the physicochemical (yield, spreadability, protein content, and moisture content) and organoleptic characteristics (taste, color, aroma, texture, and overall preference) of cream cheese made using thiol protease from frangipani stem as a substitute for animal rennet. A completely randomized design was applied for physicochemical testing, and a randomized block design was used for organoleptic testing, followed by Duncan’s Multiple Range Test. Treatments included: PK (0.2% animal rennet), P1 (0.2% frangipani stem thiol protease), P2 (0.4% frangipani stem thiol protease), and P3 (0.6% frangipani stem thiol protease). The results showed that different concentrations of frangipani stem thiol protease significantly affected (P<0.05) the physicochemical parameters (yield, spreadability, protein, and moisture content). Organoleptic evaluation also showed significant differences (P<0.05) in color, taste, aroma, texture, and overall preference. The best treatment was P3 (0.6%), with a yield of 20.68%, moisture content of 73.25%, protein content of 14.73%, and excellent spreadability